ANALYZING STUDENTS' LEARNING DIFFICULTIES IN ALGEBRA - Ralivia Suci Setianingrum; Syamsuri Syamsuri; Yani Setiani (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract:This study aimed to describe a type of student learning difficulties in algebra that associated with the indicator based on the dimensions of Bloom's Taxonomy Revision. The method used is descriptive qualitative. The subject research is students of class VIII B at SMPN 7 Kota Serang. Data collection techniques used is a diagnostic test and interview. The analysis technique used is collection, reduction, presentation of data, and conclusion. The results showed that some types of students' learning difficulties in algebra. Students have difficulties in identifying the variables, coefficients, constants, and rates similar, the difficulties in simplifying a form of algebra, the difficulties of using the properties of distributive multiplication and arithmetic operations of mathematics, the difficulties in making a mathematical model of a statement or everyday problems, the difficulties in determining the overall value, per unit, and in part, the difficulties of counting based on the unit value, difficulties in resolving problems using the properties of comparative worth, and the difficulties of reflective thinking, as well as difficulty experienced by students, lies in the factual, conceptual, procedural, and metacognitive knowledge.Abstrak:Penelitian ini bertujuan untuk mendeskripsikan jenis kesulitan belajar siswa pada aljabar berdasarkan dimensi Revisi Taksonomi Bloom. Metode penelitian yang digunakan adalah deskriptif kualitatif. Subjek penelitian adalah siswa kelas VIII B di SMPN 7 Kota Serang. Teknik pengumpulan data menggunakan tes diagnostik dan wawancara. Teknik analisis yang digunakan adalah pengumpulan, reduksi, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan jenis kesulitan belajar siswa yaitu kesulitan dalam mengidentifikasi variabel, koefisien, konstanta, dan tingkat yang serupa, kesulitan dalam menyederhanakan bentuk aljabar, menggunakan sifat-sifat perkalian distributif dan operasi matematika aritmatika, membuat model matematika, menentukan nilai keseluruhan, per unit, dan sebagian, kesulitan penghitungan berdasarkan nilai unit, kesulitan menyelesaikan masalah menggunakan sifat-sifat nilai komparatif, dan kesulitan berpikir reflektif, serta kesulitan siswa terletak pada pengetahuan faktual, konseptual, prosedural, dan metakognitif.